Machinability of UMCo50 Cobalt Superalloy - Zemčík, Oskar; Kouřil, Karel; Slaný, Martin; Zouhar, Jan; Sedlák, Josef; Kolomý, Štěpán (Manufacturing Technology Journal, 2023)
Testing of machinability of the UMCo50 superalloy was carried out within the project following the actual production of the semi-finished product by casting. Turning was chosen as the machining method to minimize the effect of an interrupted cut. Considering the machinability of a hard-to-machine alloy, the cutting material with the fine-grained WC-Co carbide with the TiN/TiAlN gradient PVD coating was selected. The progression of cutting forces, chip formation and tool wear were evaluated. Images of the material structure of the semi-finished product and the resulting chips were taken. From the measured values, graphs of the dependence of the chip thickness ratio on the cutting speed and the Taylor´s dependence of the tool durability on the cutting speed were obtained. The aim of the experiment was selection and verification of suitable cutting conditions for efficient machining of this superalloy, especially the appropriate value of the cutting speed. The recommended value of the cutting speed was 50-70 m.min-1, while the tangential component of the cutting force was in the values usual for corrosion-resistant steels.
Keywords: UMCo50; Tool wear; Cobalt; Superalloy; Taylor's formula